Knockdown of LMNB1 Inhibits the Proliferation of Lung Adenocarcinoma Cells by Inducing DNA Damage and Cell Senescence - Li, Jiangbo; Sun, Zhijia; Cui, Yingshu; Qin, Lingmei; Wu, Fengyun; Li, Yufang; Du, Nan; Li, Xiaosong (Frontiers in Oncology, 2022)
Background: Lung cancer has considerably high mortality and morbidity rate. Lung adenocarcinoma (LUAD) tissues highly express lamin B1 (LMNB1), compared with normal tissues. In this study, we knocked down LMNB1 in LUAD cells A549 and NCI-1299 to explore the effect of its inhibition on the proliferation of cells and the potential mechanism. Methods: Using bioinformatics methods, we analyzed the specificity of LMNB1 mRNA expression level in LUAD and its effect on prognosis from TCGA data. SiRNAs were used to knock down LMNB1 in the A549 cell line, and the knockdown effect was identified by western blotting and qRT-PCR. Through CCK8 cell proliferation assay, wound healing assay, TRAP, cloning formation Assay, DNase I-TUNEL assay, ATAC-seq, immunofluorescence, FISH, in vivo mouse xenograft studies, etc, we evaluated the influence and mechanism of LMNB1 on LUAD cell line proliferation in vitro and in vivo. Results: According to bioinformatics analysis, LMNB1 is substantially abundant in LUAD tissues and is associated with tumor stage and patient survival (P < 0.05). After silencing LMNB1, the rate of cell growth, wound healing, the number of transwells, and the number of cell colonies all decreased significantly (P < 0.01). With the decreased LMNB1 expression, H3K9me3 protein expression decreases, chromosome accessibility increases, P53, P21, P16 and γ-H2AX protein expression increases, and the number of senescence staining positive cells increases. At the same time, in vivo mouse xenograft experiments showed that the tumor volume of the LMNB1-silenced group was significantly reduced, compared to that of the control group (P < 0.01), and the proliferation biomarker Ki-67 level (P < 0.01) was considerably reduced. Conclusions: Overexpression of LMNB1 in LUAD cells is significant, which has excellent potential to be an indicator for evaluating the clinical prognosis of LUAD patients and a target for precise treatment.